New genera and new species of earthworms (Oligochaeta: Octochaetidae) from Western Ghats, South India - Julka, J. M.; Blanchart, Eric; Chapuis-Lardy, Lydie (Zootaxa, 2004)
Examination of earthworm material collected during the ecological studies from the Western Ghats, a biodiversity hot spot in South India, showed the existence of new genera and new species of octochaetid earthworms. Three new genera, Senapatiella with three new species (S. alfredi, S. ghatensis, S. herbettuensis), Shimodrilus with two new species (S. bhatkalensis, S. karniensis) and Herbettodrilus containing one new species (H. bahli) are erected. Other new species, Konkadrilus shimogensis, K. gatesi, Hoplochaetella lavellei, Karmiella sulvalliensis and Wahoscolex michaelseni are also described. Keys to the species of Senapatiella and Shimodrilus are provided.